India's widows - Barik, S. (Sanghamitra), 1971- (New Delhi : Adhyayan, 2009)
On the socio-economic conditions of widows in India.
Includes index.
Includes statistics.
Keywords: Widows -- India -- Social conditions; Widows -- India -- Economic conditions; Widowhood -- India